In vivo Sarcomere Lengths and Sarcomere Elongations Are Not Uniform across an Intact Muscle - Moo, Eng Kuan; Fortuna, Rafael; Sibole, Scott C.; Abusara, Ziad; Herzog, Walter (Frontiers in Physiology, 2016)
Sarcomere lengths have been a crucial outcome measure for understanding and explaining basic muscle properties and muscle function. Sarcomere lengths for a given muscle are typically measured at a single spot, often in the mid-belly of the muscle, and at a given muscle length. It is then assumed implicitly that the sarcomere length measured at this single spot represents the sarcomere lengths at other locations within the muscle, and force-length, force-velocity and power-velocity properties of muscles are often implied based on these single sarcomere length measurements. Although intuitively appealing, this assumption is yet to be supported by systematic evidence. The objective of this study was to measure sarcomere lengths at defined locations along and across an intact muscle, at different muscle lengths. Using second harmonic generation imaging technique, sarcomere patterns in passive mouse tibialis anterior (TA) were imaged in a non-contact manner at five selected locations (‘proximal’, ‘distal’, ‘middle’, ‘medial’ and ‘lateral’ TA sites) and at three different lengths encompassing the anatomical range of motion of the TA. We showed that sarcomere lengths varied substantially within small regions of the muscle and also for different sites across the entire TA. Also, sarcomere elongations with muscle lengthening were non-uniform across the muscle, with the highest sarcomere stretches occurring near the myotendinous junction. We conclude that muscle mechanics derived from sarcomere length measured from a small region of a muscle may not well represent the sarcomere length and associated functional properties of the entire muscle.